Gendered Perceptions of Writing Rubrics in Higher Education: An Exploratory Study of English Lecturers in Malaysia - Ramli, Nur Hani Laily; Baharudin, Faizah; Safian, Syahidatul Akmar; Ravdan, Ariunaa (Semarak International Journal of Current Research in Language and Human Studies, 2026)
Assessment rubrics are essential tools in higher education for ensuring transparency and consistency in evaluating student learning. While existing research has largely focused on student perspectives, there is a lack of inquiry into the role of gender in how educators perceive these tools. This exploratory study investigated the differences between male and female lecturers’ perceptions of a generic writing rubric within a Malaysian centre of foundation studies. Employing a quantitative descriptive design, data were collected from 24 English lecturers (4 males, 20 females) with teaching experience ranging from 3 to 21 years via a 16-item questionnaire. Descriptive statistics and mean comparisons revealed that female lecturers consistently rated the rubric more positively than their male counterparts, particularly regarding its role in enhancing learner skills and improving assessment practices. These preliminary findings suggest that gender may influence the perceived value of assessment tools. The study concludes that institutions should consider these divergent perspectives when designing professional development and suggests that wider, gender-inclusive engagement in rubric design is necessary to ensure departmental cohesion in assessment.